PENGARUH FAKTOR SOSIAL EKONOMI TERHADAP STATUS KESEHATAN MASYARAKAT DI KECAMATAN PALU SELATAN - Puluhulawa, Idrus (Katalogis, 2013)
The successfulness of public health in South Palu Sub-district contributes to decide the accievement of national develoment. Health population supports not only education program but also the increase of poructivity and household income. Therefore, the main problem of this research was whether the level income of household head who works at formal sector influence the public health status. Similarly, to overcome health problems in certain area is directly related to social and economic factors.In conducting this research, the reseracher applied stratified random sampling technique representing the citezens as responends in South Palu Subdistrict. Therefore, sample consisted of 5 sub-districts, 3 citizen communities, 3 household communities, and 5 household heads. The total number of sample was 126 persons. From the 12 sub-districts, the sample involved 5 subdisrticts: Tatura Utara (35 households), Birobuli Utara (30 households) Tanamodindi (22 households), Birobuli Selatan (18 households), and Tatura Selatan (21 households).After analyzing the data, this research result showed that the income of household head was about 1,500,000.- rupiahs, without social and economic factors that directly influenced toward health status, namely every individual tended to have bad health status. Other factors, such as job area, house environment, social health assurance had significant influence, a=5% with positive sign. It indicated that the head of household with job area was provided well, healthy house environment and health assurance were done better service; therefore, public health status was good for each household. Meanwhile, other factors, they were significant a=15% with negative sign on individual health characteristics, such as respondents age, gendre, long time in completing study, marital status, the head of house hold, and the number of household members did not directly influence bad health status. This results showed that the varibales tends or have opportunity to influence both bad and good health status.